PENERAPAN GOOD AGRICULTURE PRACTICES (GAP) PADA USAHATANI BUAH NAGA MERAH DI KECAMATAN PESANGGARAN KABUPATEN BANYUWANGI - Nahrul Firdaus; Illia Seldon Magfiroh; Didin Yulilenaningtyas (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
This research develops and applies the implementation of Good Agriculture Practices to red dragon fruit farming, influencing factors, and recommendations for providing extension materials to increase its implementation. Implementing Good Agricultural Practices must be by Control Points, Standard Operating Procedures, Plant Pest Control, filling out workbooks, and re-registration, which are obligations that farmers must carry out after obtaining a Good Agricultural Practices certificate. In this study, as many as 62 red dragon fruit farmers certified as Good Agriculture Practices were selected as a whole or total sampling. The Likert scale is used to analyze the level of implementation of Good Agriculture Practices. Logistic Regression Analysis is used to see the factors that influence the level of implementation of Good Agriculture Practices. Efforts to increase the implementation of Good Agricultural Practices through rankings. The research results show that (1) the implementation of Good Agriculture Practices in red dragon fruit farming is sufficient; (2) factors that influence the implementation of Good Agriculture Practices are the variables of farming experience, perception of production quantity, and perception of selling price. (3) recommendations for increasing the implementation of Good Agriculture Practices in red dragon fruit farming in Pesanggaran District can be done by providing material on priority efforts starting from Mandatory Control Points, Very Green Control Points, filling out workbooks, implementing Plant Pest Control, re-registering, Points Control Recommendations, and implementation of Standard Operating Procedures.